2013
DOI: 10.3389/fphys.2013.00103
|View full text |Cite
|
Sign up to set email alerts
|

Protection of rat skeletal muscle fibers by either L-carnitine or coenzyme Q10 against statins toxicity mediated by mitochondrial reactive oxygen generation

Abstract: Mitochondrial redox imbalance has been implicated in mechanisms of aging, various degenerative diseases and drug-induced toxicity. Statins are safe and well-tolerated therapeutic drugs that occasionally induce myotoxicity such as myopathy and rhabdomyolysis. Previous studies indicate that myotoxicity caused by statins may be linked to impairment of mitochondrial functions. Here, we report that 1-h incubation of permeabilized rat soleus muscle fiber biopsies with increasing concentrations of simvastatin (1–40 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
0
28

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(88 citation statements)
references
References 71 publications
(112 reference statements)
7
53
0
28
Order By: Relevance
“…We already know that CoQ 10 participates in the electron transport chain in mitochondria (27) and that statins can interfere with CoQ 10 , compromising cellular energy production (28). La Guardia et al (29) have demonstrated that simvastatin inhibits mitochondrial respiration, depletes CoQ 10 , and increases hydrogen peroxide production. A small increase in CoQ 10 concentration in mitochondrial membranes can therefore restore mitochondrial respiration (7) as one of the mechanisms to protect liver cells from statin toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…We already know that CoQ 10 participates in the electron transport chain in mitochondria (27) and that statins can interfere with CoQ 10 , compromising cellular energy production (28). La Guardia et al (29) have demonstrated that simvastatin inhibits mitochondrial respiration, depletes CoQ 10 , and increases hydrogen peroxide production. A small increase in CoQ 10 concentration in mitochondrial membranes can therefore restore mitochondrial respiration (7) as one of the mechanisms to protect liver cells from statin toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Although the molecular mechanisms underlying statin-induced myotoxicity are not yet fully understood, a common hypothesis suggests that it is mediated by inhibition of mitochondrial respiration as a consequence of CoQ 10 depletion (Päivä et al, 2005; Bookstaver et al, 2012; Larsen et al, 2013). In addition, previous studies propose that statins cause cell death associated with alterations in calcium homeostasis, inhibition of beta-oxidation, inhibition of mitochondrial respiratory complexes I and II followed by mitochondrial oxidative stress (Kaufmann et al, 2006; Oliveira et al, 2008; Costa et al, 2013; La Guardia et al, 2013) and also inhibition of complex III (Schirris et al, 2015). We have previously shown that statins stimulate Ca 2+ induced mitochondrial permeability transition (MPT) in mitochondria isolated from murine liver and muscle, and from mice treated with lovastatin (Velho et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen protects skeletal muscles through its antioxidant effect (Sotiriadou et al, 2003). Statins' myopathy, mainly postulated to cause oxidative damage of the mitochondrial respiratory chains, is reversed by L-carnitine and CoQ10 through their direct radical scavenging effects (La Guardia et al, 2013). Simvastatin's myopathy impairs phosphatidylinositol 3-kinase/Akt signaling in rodent skeletal muscle (Mallinson et al, 2012).…”
Section: Fig 3 Effects Of Treatments (For Eight Weeks) On Serum Levementioning
confidence: 99%
“…L-Carnitine, besides its metabolic role, has an antioxidant effect and can directly decrease superoxide radical generation. CoQ10 is an essential electron transporter in the respiratory chain and its reduced form (ubiquinol) shows antioxidant properties (Young et al, 2011;Bookstaver et al, 2012;La Guardia et al, 2013). Simvastatin increases cytoplasmic Ca 2+ triggering mitochondrial reactive oxygen generation and myotoxicity (Sirvent et al, 2005a).…”
Section: Introductionmentioning
confidence: 99%